ELECTRON MICROSCOPIC DETECTION OF POTATO VIRUS A USING GOLD NANO PARTICLES - Raigond, Baswaraj; Jevalatha, A; Singh, B P; Kochhar, Tarvinder (Potato Journal, 2013)
A study was initiated to detect Potato virus a (PVA) in infected potato plants by immuno-gold electron microscope. PVA particles were completely purified and polyclonal antibody was raised by immunizing the rabbit. The specificity of the antibody obtained was confirmed by DAS-ELISA wherein the antibodies reacted specifically with PVA. The IgG was purified and examined by DAS-ELISA for determination of optimum concentration with different dilutions, wherein 1:800 gave good reaction. After confirming the specificity, the purified IgG was conjugated with colloidal gold nano particles. The IgG conjugated with gold nano particles in the electron microscopic examination showed a good concentration of filamentous flexuous long particle coupled with several colloidal gold (CG) nano particles revealing the presence of PVA. More than one IgG-CG complex was associated with each PVA particle indicating its successful conjugation with gold particles. Since only the homologous virus will be decorated with IgG-CG complex, it can be used for specific detection and diagnosing a targeted virus even in mixed infection of viruses with similar morphology. Thus this technique can be used successfully for detection or screening of PVA in potato plant samples.